Parents and Children Should Be More Active Together to Address Physical Inactivity and Sedentary Behaviours - Rainham, Daniel G; Bennett, Mark; Blanchard, Christopher M; Kirk, Sara FL; Rehman, Laurene; Stone, Michelle; Stevens, Daniel (Frontiers in Public Health, 2022)
Increasing rates of physical inactivity and sedentary behaviours among children and youth are important determinants of chronic disease. Supporting children’s participation in organized physical activities like sports has been promoted as a public health strategy to increase physical activity. Evidence shows that successful interventions are family-focused although research on how parental eating and physical activity behaviours influence children’s behaviours is deficient. In this commentary, we argue that interventions to counter physical inactivity and sedentary behaviours should include a greater focus on home and social environments, specifically the influence and involvement of parents, siblings, and friends in supporting these health behaviours. We conclude that the design of interventions to prevent chronic diseases in children should also more fully consider the conditions within which the behaviours of children and their parents occur. This means encouraging parents and children to be active together to address physical inactivity and sedentary behaviours, while being mindful of unintended consequences from a focus on one behaviour over another..